Genetic analysis of indel markers in three loci associated with Parkinson's disease. - Zhixin Huo; Xiaoguang Luo; Xiaoni Zhan; Qiaohong Chu; Qin Xu; Jun Yao; Hao Pang (PLoS ONE)
The causal mutations and genetic polymorphisms associated with susceptibility to Parkinson's disease (PD) have been extensively described. To explore the potential contribution of insertion (I)/deletion (D) polymorphisms (indels) to the risk of PD in a Chinese population, we performed genetic analyses of indel loci in ACE, DJ-1, and GIGYF2 genes. Genomic DNA was extracted from venous blood of 348 PD patients and 325 age- and sex-matched controls without neurodegenerative disease. Genotyping of the indel loci was performed by fragment length analysis after PCR and DNA sequencing. Our results showed a statistically significant association for both allele X (alleles without 5) vs. 5 (odds ratio = 1.378, 95% confidence interval = 1.112-1.708, P = 0.003) and genotype 5/X+X/X vs. 5/5 (odds ratio = 1.681, 95% confidence interval = 1.174-2.407, P = 0.004) in the GIGYF2 locus; however, no significant differences were detected for the ACE and DJ-1 indels. After stratification by gender, no significant differences were observed in any indels. These results indicate that the GIGYF2 indel may be associated with increased risk of PD in northern China.